The Determinants of Postsecondary Enrolment Rates in Ontario - Foot, David K.; Pervin, Barry (Canadian Journal of Higher Education, 1983)
This paper examines the determinants of postsecondary enrolment rates in Ontario in the context of economic theories of educational demand. The traditional consumption and investment theories are found to provide significant determinants of observed enrolment rates, especially for universities. Community college enrolments appear to be more income sensitive than university enrolments and, within the university student body, graduate enrolments appear to be more price sensitive than undergraduate enrolments. In addition, an indicator of cohort size is shown to have a depressing effect on enrolment rates. No significant effects of "competition" between universities and community colleges are discerned. The results are used to account for the stabilization in postsecondary enrolment rates in Ontario over the 1970s and to provide insights into likely future developments. Illustrative calculations suggest that, on average, enrolment rates in postsecondary institutions are likely to increase over the 1980s, primarily as a result of increasing per capita incomes and declining cohort sizes. Consequently, the often anticipated decline in postsecondary enrolments is unlikely to materialize and public policies towards postsecondary institutions, especially universities, must be careful to incorporate this information.